PELAKU UTAMA DIBALIK KEPUTUSAN MEETING PLANNER DALAM MENENTUKAN DESTINASI MICE - I Gusti Made Wendri; I Made Budiasa (Politeknik Negeri Bali, 2013)
This research tries to obtain certain information about such agents as company, association, potential delegates, PCO and destination attributes behind the decision making of meeting planner in determining MICE’s destination. The data of this research are gained from 7 international journal articles and book chapters relating to the topic of discussion. The methods of analysis is based on descriptive qualitative approach by describing the data as it is.